Tourette Syndrome: Complementary Insights from Measures of Cognitive Control, Eyeblink Rate, and Pupil Diameter - Tharp, Jordan A.; Wendelken, Carter; Mathews, Carol A.; Marco, Elysa J.; Schreier, Herbert; Bunge, Silvia A. (Frontiers in Psychiatry, 2015)
Some individuals with Tourette Syndrome (TS) have severe motoric and vocal tics that interfere with all aspects of their lives, while others have mild tics that pose few problems. We hypothesize that observed tic severity reflects a combination of factors, including the degree to which dopaminergic (DA) and/or noradrenergic (NE) neurotransmitter systems have been affected by the disorder, and the degree to which the child can exert cognitive control to suppress unwanted tics. To explore these hypotheses, we collected behavioral and eyetracking data from 26 patients with TS and 26 controls between ages 7 and 14, both at rest and while they performed a test of cognitive control. To our knowledge, this is the first study to use eyetracking measures in patients with TS. We measured spontaneous eyeblink rate as well as pupil diameter, which have been linked, respectively, to DA and NE levels in the central nervous system. Here, we report a number of key findings that held when we restricted analyses to unmedicated patients. First, patients’ accuracy on our test of cognitive control accounted for fully 50% of the variance in parentally reported tic severity. Second, patients exhibited elevated spontaneous eyeblink rates compared to controls, both during task performance and at rest, consistent with heightened DA transmission. Third, although neither task-evoked pupil dilation nor resting pupil diameter differed between TS patients and controls, pupil diameter was positively related to parentally reported anxiety levels in patients, suggesting heightened NE transmission in patients with comorbid anxiety. Thus, with the behavioral and eyetracking data gathered from a single task, we can gather objective data that are related both to tic severity and anxiety levels in pediatric patients with TS, and that likely reflect patients’ underlying neurochemical disturbances.